Telephone excellence - Wilson, Main; Dowling, Roger (North Adelaide : Video Communicators, 1900)
Summary:'This video demonstrates the basic skills involved in telephone communication. It talks about customers and the effect on telephone behaviours have on them.'...catalogue
Copy available in DVD format.
Camera, Jeff Clayfield.
Keywords: Telephone etiquette